Economic- Juristic Analysis of Usury in Consumption and Investment Loans and Contemporary Jurisprudence Shortages in Exploring Legislator Commandments - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
In this article, by analyzing the deduction methodology of jurisprudence commandments, we try to touch the existing shortages in its methodological aspects. By discussing on different sources of Islamic jurisprudence like the Quran, Sunna (Tradition), consensus, intellect, fame, analogy, preference, public interest considering, blocking the means, we will explicates that the divine authority (person who is allowed by the messenger or by someone whom messenger has allowed him) has been ignored in religious deduction, and thus these different ideas have emerged in Islamic commandments. In this regards, juristic decrees may be compared, which are different and even conflict solutions to a unique problem or question. These conflicts enlighten two important propositions. • The juristic deduction methodology needs revision. • Ignorance to theosophy principle of jurisprudence is the main source of conflicts. By defining and analyzing usury and interest in an economic-juristic frame and specifically in the Quran and with respect to wisdom or theosophy principle in jurisprudence to distinguish usury and non-usury finance, we conclude: • The loaner must share in profit and loss of the economic activity of the loan receiver. • The rate of interest-because of inability to determine the capital productivity rate a priori- should not be determined and conditioned in advance. • Receiving interest in consumption loans is usury and not allowed. Transformation of credit and deposit markets’ oscillations to the real sector is the main initiation of real sector economic fluctuations. Respect to wisdom (theosophy) principle of religious legislation, and by introducing a mathematical model, we show that usury causes economic fluctuations and by deleting usury from the economy, we conclude that real economy will be more stable. DOI: https://doi.org/10.5281/zenodo.3402329